نفي الکمال والصحة عند الأصولیین والفقهاء: دراسة أصولیة مقارنة - المصباحي، أحمد بن محمد بن إسماعيل Almesbahi, Ahmed Bin Mohammed Bin Ismail (جامعة الأزهر - کلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2018)
تزخر كتب الفقهاء و الأصوليين بثروة وافرة من التأصيل و التطبيق لمصطلح " النفي " مستندة إلى نصوص الكتاب و السنة ، معتمدة على المباحث اللغوية والنحوية المبيّنة لدلالة النفي ومراتبه ، فتارة يتوجه النفي إلى الصحة، وتارة يتوجه النفي إلى الكمال ، وتاره يتوجه النفي إلى القبول، فيحتاج المكلف إلى معرفه المعنى الشرعي المراد ، وتوجيهه حال الاطلاع على نصوص الوحيين في موضوع منفي؛ ليكون على دراية تامة واطلاع حقيقي على حجم المخالفة المنفية ، ومدى تأثيرها على بطلان الأمر أو نقصان الأجر ؛وهذا البحث أصولي وفقهي، بساطه وبناؤه لغوي ونحوي، تزدوج فيه المعارف وتتزاحم فيه العلوم وتتداخل، يسلط الضوء هذه المعاني الدقيقة ويكشف مراداتها، و يفصح عنها تأصيلا وتقعيدا، وبيان أمثلة و تطبيقا، وبالله التوفيق .
Perfection and Correctness with Fundamentalists and Jurists: Comparative fundamentalism study Abstract Scholars and fundamentalists' books are full of abundant wealth for rooting and applying of the term "negation" based on the texts of Quraan and Sunna and linguistics and syntactic researches, set out to denote the term "negation" and its rank. The term "negation" is sometimes heading either to correctness, perfection or acceptance. The person incharge needs to be aware of the intention of Islamic rules and directing the rule once he or she comes across the Revelation texts that entail a negative issue, that is to be fully aware of the magnitude of negative violation and the extent of its impact on the invalidity of the order or decrease in rewards. This research is fundamentalist, jurisprudential, simple and linguistically and grammatically constructed, where knowledge is duplicated and the sciences are intertwined and overlapped. It sheds light on these precise meanings and reveals them fundamentally and ruling-based, illustrated with examples and application.
Keywords: الفقه الإسلامى -- علم أصول الفقه -- علوم اللغة -- نفی الکمال والصحة